Mapping of Sensing Performance of Concentric and Non-Concentric Silver Nanoring - Mulda Muldarisnur; Ilham Perdana; E. Elvaswer; Dwi Puryanti (Ital Publication, 2023)
Sensors play a critical role in improving overall human quality of life. They have been employed in most aspects of our lives. A recently emerging sensing platform is based on plasmonic resonance at the boundary of metals and dielectrics. Localized surface plasmon resonances–based sensors offer miniaturization, a simple setup, and relatively high sensitivity for real-time measurements. The reported figure of merit (FOM) of the LSPR-based sensor is generally limited, primarily due to its broad resonance peak. Nanorings composed of metal nanoparticles are known for their broad-range resonance tunability, high field localization, and large sensing area. Asymmetry of the nanoring with the introduction of core offset relaxes the selection rule for mode mixing, thus resulting in a narrower resonance peak. This may overcome broad resonance peak restriction. Concentric and non-concentric nanorings were simulated using the boundary element method implemented with the MNPBEM toolbox. We map the performance of nanoring sensors over a wide range of geometrical variations, namely, diameter, ring shell thickness, and the offset of the inner ring to the center of the outer ring wall (core offset). Sensitivity and FOM were found to rely substantially on the nanoring size parameters. The sensing performance map helps to obtain optimized nanoring parameters for the intended spectral range region. The obtained high sensitivity and FOM are much higher than the data available in the literature over visible and NIR ranges. The findings demonstrate the potential of nanorings for biosensing applications. Doi: 10.28991/ESJ-2023-07-04-04 Full Text: PDF